(untitled) (Journal of the College of Languages (JCL), 2013)
The weak and strong forms are so called because it is not their lexical content that primary matter, but the role they have in the sentence. The problematic confusion, our students encounter, in recognizing and producing the correct pronunciation of weak and strong forms of the English function words is the main incentive behind conducting this study. In order to gather the data, this paper used two types of tests: a recognition test and a production test. The general results reached through the analysis of the students’ answers seem to conform to the researcher’s assumption: students face a critical problem in recognizing and producing correct pronunciation of the weak and strong forms of the English function words.